PEMBUATAN BUKU KOMIK MONUMEN DI KOTA SURABAYA SEBAGAI UPAYA PENGENALAN SEJARAH KEPADA REMAJA - Maulana, Pam Pam Januar; Bahruddin, Muh; Dewanto, Thomas Hanandry (Jurnal Art Nouveau, 2014)
The rapid development occurring in large cities such as Surabaya, making people, especially teenagers are getting no matter against the objects surrounding historical heritage such as monuments. In fact, the Monument serves to recall an incident as well as the figure of the hero who fought for independence has become one of the citys tourism icon of Surabaya as a town hero. This is unfortunate, especially when reviewing many tourists domestic and non domestic who visited Surabaya city just to see the existing monuments as silent witnesses of history of war in the city of Surabaya. In addition, yet there is also a media information about the monument to youth in the form of comics. If the above issues are left alone, then the next generation wont be acquainted with the history and purpose of making existing monuments nearby.